Existential Philosophy of Etty Hillesum : An Analysis of Her Diaries and Letters. - Coetsier, Meins G. S. (Supplements to The Journal of Jewish Thought and Philosophy, 2014)
In The Existential Philosophy of Etty Hillesum Meins G.S. Coetsier breaks new ground by demonstrating the Jewish existential nature of Etty Hillesum's spiritual and cultural life in light of the writings of Martin Buber, Emmanuel Levinas and Dietrich Bonhoeffer. Hillesum's diaries and letters, written between 1941 and 1943, illustrate her struggle to come to terms with her personal life in the context of the Second World War and the Shoah. By finding God under the rubble of the horrors, she rediscovers the divine presence between humankind, while taking up responsibility for the Other as a way to embrace justice and compassion. In a fascinating, accessible and thorough study, Coetsier dispels much of the confusion that assails readers when they are exposed to the bewildering range of Christian and Jewish influences and other cultural interpretations of her writings. The result is a convincing and profound picture of Etty Hillesum's path to spiritual freedom.